Attitudes toward Divorced Women Scale and Its Associations with Ambivalent Sexism and Demographic Variables. Issue 7 (3rd October 2021) - Manuoğlu, Elif; Sakallı, Nuray; Koskos-Gürel, Didem
ABSTRACT: The purposes of this study were to develop a Likert type of scale on attitudes toward divorced women (ADW), and to test its associations with hostile sexism (HS), benevolent sexism (BS), and demographic variables which, in return, provide evidence for construct-convergent validity. An item pool of ADW scale was administered to participants along with Ambivalent Sexism Scale and demographic information via an online survey. Results from 444 participants (296 female; Mage = 25.11, SDage = 7.58) provided a valid and reliable scale including three subfactors, negative perception about divorced women (α = .89) strength of divorced women (α = .73), and prescriptive social norms for divorced women (α = .91). There were associations among the subfactors and HS/BS.